Impact of healthcare access and socio-economic conditions on prevalence of metabolic syndrome: evidence from 2015 BRFSS. (24th June 2020) - Joshi, Praphul; Ghosh, Kaushik; Natarajan, Vivek S.; Mandal, Purnendu
Metabolic syndrome (MetS) is a major public health challenge in the USA and elsewhere. MetS generates high costs to national healthcare system, as well as causing deteriorating health condition in individuals. Studies indicate that MetS may be influenced by demography, race, income, education level and access to healthcare system. Using 2015 national survey data - Behavioural Risk Factor Surveillance System (BRFSS) - this article analyses the prevalence of MetS across ethnic and socio-economic sections of population. The analysis supports the prevailing knowledge that MetS is influenced by access to healthcare, race, income and education level of population. An interesting finding of this work is that those who reported not having any kind of health coverage had a significantly lower prevalence of MetS compared to those who reported having health coverage.